Analisis Kesesuaian Tutupan Lahan Tahun 2040 terhadap Pola Ruang Ruang Wilayah Kabupaten Rokan Hulu Tahun 2020-2040 - Ramanda, Akbar; Syahar, Fitriana (Al-DYAS, 2024)
This study aims to: a) Analyze the land cover in 2022 in Rokan Hulu Regency. b) Analyze the suitability of land cover in 2022 against the spatial patterns in Rokan Hulu Regency. c) Predict the land cover in 2040 in Rokan Hulu Regency. d) Analyze the suitability of the predicted land cover in 2040 against the spatial patterns in Rokan Hulu Regency. The method used in this study is quantitative research. The data analysis techniques include image interpretation sourced from SPOT 6/7 and Sentinel 2 imagery, cellular automata (CA), and overlay. Based on the results of this study, it can be concluded that the land cover in Rokan Hulu Regency consists of 6 classes: forest, built-up land, open land, water bodies, agriculture, and shrubs. In 2022, the area of forest land cover is 81,112.20 ha, built-up land is 10,214.72 ha, open land is 7,368.03 ha, water bodies are 12,851.11 ha, agriculture is 711,265.76 ha, and shrubs are 239.62 ha, with a suitability level against the spatial pattern of 51.33%. In 2040, the area of forest land cover is 85,462 ha, built-up land is 10,226 ha, open land is 2,745 ha, water bodies are 16,300 ha, agriculture is 704,256 ha, and shrubs are 4,060 ha, with a suitability level against the spatial pattern of Rokan Hulu Regency of 47.9%.